Albendazole nanocrystals with improved pharmacokinetic performance in mice. (February 2018) - Paredes, Alejandro J; Bruni, Sergio Sánchez; Allemandi, Daniel; Lanusse, Carlos; Palma, Santiago D
Aim: Albendazole (ABZ) is a broad-spectrum antiparasitic agent with poor aqueous solubility, which leads to poor/erratic bioavailability and therapeutic failures. Here, we aimed to produce a novel formulation of ABZ nanocrystals (ABZNC) and assess its pharmacokinetic performance in mice.Results/methodology: ABZNC were prepared by high-pressure homogenization and spray-drying processes. Redispersion capacity and solid yield were measured in order to obtain an optimized product. The final particle size was 415.69±7.40 nm and the solid yield was 72.32%. The pharmacokinetic parameters obtained in a mice model for ABZNC were enhanced (p < 0.05) with respect to the control formulation.Conclusion: ABZNC with improved pharmacokinetic behavior were produced by a simple, inexpensive and potentially scalable methodology.